“The play’s the thing”: A Farcical Re-writing of Hamlet as Subversive Anti-Totalitarian Discourse - Oana Celia GHEORGHIU (ACROSS)
Polonius, Romanian author Victor Cilincă’s farcical rewriting of Hamlet, is worth mentioning among the many postmodernist adaptations of Shakespeare’s works, despite the fact that it is virtually unknown to both theatregoers and critics. The play premiered in 1996, in Galati, having been ‘hidden’ in the writer’s drawer for more than a decade for fear that censorship might grasp its anti-totalitarian implications. In 2011, it was translated by Petru Iamandi for an American indie press.